The Guidelines for the Cooperation of Parents and Schools: What Does the Analysis of Critical Feedback from Parents Reveal About the Educational Process - Čiuladienė, Gražina; Valantinas, Antanas (Acta Paedagogica Vilnensia, 2016)
Parental involvement has a positive impact on children’s learning achievements, school attendance etc. There is a lack of research of the involvement of parents in the extent of school life as well as the advantages and obstacles posed by it in Lithuania. The purpose of this article is to find out the voltage fields in parent – teacher relationship. Parents’ opinions about the school’s activities survey data (the survey was held by the National School Assessment Agency at 2010-2012 year) was analyzed for this study. Only online comments of the parents were analyzed and only remarks of the negative nature were considered (420 respondents). The data were analyzed on the basis of grounded theory (V. Ћydћiūnaitė, 2006, 2007; B. Bitinas, 2006). This article discusses only one conceptual category – the poor quality of education. Content analysis of the comments discussing the quality of education allows us to distinguish four sub-categories: teaching inefficiency, the lack of support, the lack of discipline and the disadvantages of achievements and progress. According to the analysis of survey results, it can be said that the parents‘ dissatisfaction with the quality of the teaching process gives birth to distrust in the quality of school teacher competency, which further alienates parents from the school. Such an atmosphere of communication, one based on the distrust and dissatisfaction of parents, lays ground for deep conflict situations rather than well-wishing cooperation, which is conducive to parental involvement in children’s education.